Wild pink bayberry fruit: the effect of in vitro gastrointestinal digestion on phytochemical profiles, and antioxidant and antiproliferative activities. Issue 5 (10th February 2021) - Xia, Wen; Lin, Yanyun; Gong, Ersheng; Li, Tong; Lian, Fengli; Zheng, Bisheng; Liu, Ruihai
Abstract : In general, pink bayberry cultivar, a vital source of polyphenols, showed strong antiproliferative activity after digestion at the end of the intestinal and colon steps, which can be considered as a dietary supplement. Abstract : The regular consumption of polyphenol-rich foods is essential to prevent the onset of diseases. Wild fruits are known to possess higher levels of bioactive components than the domesticated fruits because of the severe environmental conditions they are grown in. The aim of this study was to evaluate the phytochemical profiles, and antioxidant and antiproliferative activities of a wild pink bayberry fruit after in vitro digestion and to compare them with results obtained with a chemical extraction method. A low release of total phenolics and anthocyanins was observed after digestion compared with chemical extraction, while more flavonol contents were found by HPLC analysis. The digesta samples demonstrated low levels of extracellular antioxidant activity (EAA) and cellular antioxidant activity (CAA). However, the cellular uptake rate was increased during the in vitro digestion, and the largest value of 75.35% was obtained in the colon step. Notably, the antiproliferative activity in the colon digesta (10.14 ± 0.13 mg mL −1 ) was close to that of extracts (7.6 ± 0.63 mg mL −1 ). Pearson correlation analysis revealed that EAA and CAA were significantly correlated with TPC, while the antiproliferative activity was significantly correlated with the total contents of three flavonol compounds (quercetin, kaempferol, and myricetin). Our observations provide new insights into the bioactivity variation of whole fruits as affected by simulated digestion.